PENGARUH PENGGANTIAN SEBAGIAN JAGUNG DENGAN TEPUNG KULIT PISANG RAJA (Musa paradisiaca) DALAM RANSUM TERHADAP PERFORMAN BROILER - Djapili, David; Wolayan, Fenny; Untu, Ivonne; Liwe, Hengki (ZOOTEC, 2016)
ABSTRACT EFFECT OF SUBSTITUTION OF YELLOW CORN WITH BANANA (Musa paradisiaca) PEELS IN THE DIETS ON BROILER PEERFORMANCE. A study has been conducted to determine the effect of substitution of yellow corn with banana (Musa paradisiaca) peels in the diets on broiler performance. The present study used 60 broiler chicks and reared for 5 weeks. A Completely Randomized Design was used as an experimental design with 4 treatments and 5 replications. Treatments were formulated as follow: R0: diet without substitution of banana peels or 0% in the diet; R1: diet with the substitution of 7,5% or 4,28% in the diet; R2: diet with the substitution of 15,0% or 8,55% in the diet; and R3: diet with the substitution of 22,5% or 12,83% in the diet. Variables measured were: daily feed consumption, daily gain, and feed conversion. Research results showed that daily feed consumption, daily gain, and feed conversionratio were all significantly (P < 0,05) affected by treatments. Daily feed consumption at R3 significantly (P < 0,05) lower compared with R0 and R1 treatments, but no differences (P > 0,05) were observed  between R2 and R3. No significant (P > 0,05) was observed between R0 and R1, but there was a significant difference (P < 0,05) between R2 and R3 and between R1 and R2. Feed conversion ratio was significantly (P < 0,05) lower for R0 compared with R1, R2 and R3, but no differences (P > 0,05) were observed among R0, R1, and R2 treatments. It can be concluded that banana (Musaparadisiaca) peels meal can be used up to 15% replacing yellow corn or 8,55% in broiler diet. Key words: Broiler chicks, Banana    (Musaparadisiaca) peels,        Daily feed consumption,         Daily gain, feed conversion            ratio.